Studi Perbandingan Tafsir Al-Tahrir wa al-Tanwir dan Tafsir Al-Manar terhadap Konsep Jihad: Analisis Redaksi Kata Jihad dan Qitāl - Muhammad Luqman Hakim Al Qindi; Nanda Aminata; Muhammad Rafly; Abu Bakar (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2025)
This article discusses one of the interpretive approaches that cannot be separated from the attention of the mufasir, namely thematic interpretation. This research aims to explore the meaning of jihad in the perspective of thematic interpretation, especially on the redaction of the word jihad in the Qur'an. The object of research used focuses on the redaction of words in the Qur'an that represent jihad, namely jihad and qitāl. The research method used is a qualitative approach with a text analysis study. The primary sources used are two books of tafsir that use ijtima'i context, or better known as thematic, as an approach. The two books of tafsir are al-Tahrir wa al-Tanwir by Ibn 'Assyria and Tafsir al-Manar by Rasyid Ridha. Secondary sources used are some previous studies related to the research theme. The result of this study is the discovery of differences in the meaning of the editorial words jihad and qitāl in the context of jihad. The redaction of the word qitāl is only limited to the context of warfare. While the redaction of the word jihad has a broader and more complex meaning, not only limited to the context of warfare.